Uji Bioaktivitas Antibakteri Senyawa murni dari Jamur Endofit Sporothrix sp Terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Dewi Yudiana Shinta; Yusmarini Yusmarini; Herix Sonata MS; Hilwan Yuda Teruna; Saryono Saryono (Universitas Riau, 2019)
Modern medicines that are developing now come from active ingredients isolated from plants that require large amounts of plants. The development of new drugs from endophytic fungi found obstacles in the amount of pure compounds produced. Therefore further research is needed by using endophytic fungi as a new antimicrobial producer. This study aims to see the ability or activity of pure compounds produced by Sporothrix sp endophytic fungi from Dahlia tuber (Dahlia variabilis). Test the activity of pure compounds produced by Sporothrix sp. Endophytic fungi on E. coli and Staphylococcus aureus determined by disc diffusion method. With doses of 10, 30 and 50μg/disk. In Escherichia coli bacteria doses 10 and 50μg/disk gave significant inhibition of pure compounds from isolation compared to the positive control of ciprofloxacin, which was marked by a statistically significant test result (p <0.05). In contrast to Staphylococcus aureus there was no significant difference in doses of both doses of 10.30 and 50μg/disk. Determination of pure compounds was carried out by HPLC and Infra Red Spectrophotometry.